Public health concern on occupational hazards among pathologists and microbiologists in Mysuru district, India - Sunil Kumar, D.; Anup, G.; Kulkarni, Praveen; Shabadi, Nayana; Narayana Murthy, M. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Highly qualified and trained medical specialists such as Pathologists and Microbiologists who need to work at the microscope for long hours are at a high risk of musculoskeletal and ophthalmic disorders. This study is an attempt to identify such potential occupational hazards with the objectives to estimate the magnitude of occupational hazards among Pathologists and Microbiologists in Mysuru, and to assess the factors influencing these hazards among the study participants. Methods: This cross-sectional study was conducted among the Pathologists and Microbiologists of Mysuru district over a period of six months, a total of 45 study participants were included. An online self-administered questionnaire was sent to the study participants through e-mail and asked to fill and submit online, keeping complete confidentiality, and with informed consent. The results were analysed using appropriate statistical methods. Results: Pathologists and Microbiologists in almost equal proportions consented and took part in the study. 67% of them reported work related musculoskeletal problems, and 42% had visual refractive errors, mostly myopia. 9% of them reported to have experienced occupational injuries, mostly needle-stick injuries. None of them reported to smoke. Majority were happy with the work atmosphere and environmental conditions. Most of them were positive about the work-related situation in the coming years. Conclusions: This study found that more than half of the pathologists and microbiologists are exposed to occupational hazards and have suffered musculoskeletal, ophthalmic morbidities and had injuries, but none of which were life-threatening. Most of the risk factors are avoidable through ergonomic equipment and training.